Blood glucose testing and primary prevention of diabetes mellitus type 2 - evaluation of the effect of evidence based patient information - Giani Guido; Roden Michael; Nowotny Bettina; Rathmann Wolfgang; Cole Dennis; Verheyen Frank; Steckelberg Anke; Müller Hardy; Meyer Gabriele; Haastert Burkhard; Genz Jutta; Mielck Andreas; et al. (BMC, 2010)
Abstract Background Evidence-based patient information (EBPI) has been recognised as important tool for informed choice in particular in the matter of preventive options. An objective, on the best scientific evidence-based consumer information about subthreshold elevated blood glucose levels (impaired fasting glucose and impaired glucose tolerance) and primary prevention of diabetes, is not available yet. Thus we developed a web-based EBPI and aim to evaluate its effects on informed decision making in people 50 years or older. Methods/Design We conduct a web-based randomised-controlled trial to evaluate the effect of information about elevated blood glucose levels and diabetes primary prevention on five specific outcomes: (i) knowledge of elevated blood glucose level-related issues (primary outcome); (ii) attitudes to a metabolic testing; (iii) intention to undergo a metabolic testing; (iv) decision conflict; (v) satisfaction with the information. The intervention group receives a specially developed EBPI about subthreshold elevated blood glucose levels and diabetes primary prevention, the control group information about this topic, available in the internet. The study population consists of people between 50 and 69 years of age without known diabetes. Participants will be recruited via the internet page of the cooperating health insurance company, Techniker Krankenkasse (TK), and the internet page of the German Diabetes Centre. Outcomes will be measured through online questionnaires. We expect better informed participants in the intervention group. Discussion The design of this study may be a prototype for other web-based prevention information and their evaluation. Trial registration Current Controlled Trial: ISRCTN22060616.